UBI JALAR UNGU SEBAGAI PENGGANTI TEPUNG TAPIOKA DAN EFEKNYA TERHADAP KUALITAS SENSORIS NUGGET DAGING AYAM - Derlin Elisabeth Mankutty; Nafly Comilo Tiven; Isye Jean Liur (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study was conducted to assess the effect of replacing tapioca flour with purple sweet potato flour (Ipomoea batatas L.) on the sensory properties of chicken nuggets. The research design was experimental. Chicken nuggets were made using a mixture of ingredients, namely 200 grams of ground broiler chicken, 100 grams of tapioca flour, 125 grams of ice cubes, two tablespoons of full cream milk, 15 grams of garlic, and 5 grams of salt. Substitution treatments were carried out in five groups: P0 (no replacement), P1 (25% replacement), P2 (50% replacement), P3 (75% replacement), and P4 (full or 100% replacement) with purple sweet potato flour. Sensory tests were conducted by 35 panelists using the hedonic method to assess the color, aroma, texture, and taste of the product. Data were analyzed using analysis of variance (ANOVA) based on a Completely Randomized Design (CRD) with five treatments and 35 replications. The results showed that treatment P1 (25% purple sweet potato flour) obtained the highest score significantly in color (P<0.05), aroma (P<0.01), and texture (P<0.05). Based on these results, it was concluded that substitution of 25% purple sweet potato flour in chicken nugget dough was able to improve the sensory characteristics of the product, especially in the aspects of color, aroma, and texture.